Success factors in the implementation of statistical process control: action research in a chemical plant - Jose Carlos de Toledo; Fabiane Letícia Lizarelli; Manoel Bispo Santana Junior (Production)
Abstract Despite the Statistical Process Control (SPC) be extensively explored in the literature, there are still difficulties in the implementation and maintenance, usually due to lack of attention to Critical Success Factors (CSF). This paper identified by literature review, critical factors that contribute to the success of the SPC and through an action research was implemented a control chart in a chemical plant using these factors. The attention to CSF during planning, implementation and the discussion with the process team resulted in the implementation and acceptance of control charts by the operational teams of the company, with continuing indications of use. The results enabled a framework to apply control charts based on CSF.